Biological carbon pump efficiency in the Humboldt current system off Peru: temperature, salinity and oxygen - Engel, Anja (In: Engel, Anja; Cisternas-Novoa, Carolina; Hauss, Helena; Kiko, Rainer; Le Moigne, Frédéric A C (2023): Biological carbon pump efficiency in the Humboldt current system off Peru: sediment traps during METEOR cruises M136 and M138 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963289, 2023)
Temperature, salinity and oxygen are measured using sediment traps. The particle interceptor traps were deployed six times (T1, T2, T3, T4, T6, T7) at different locations off Peru (12.0°S-14.6°S and 77.3°W-78.6°W) during the RV METEOR cruises M136 and M138 at four times in April and two times in June 2017.